WANITA 28 TAHUN P1A0 DENGAN HEMORRHAGE POST PARTUM EC SISA PLASENTA DAN ATONIA UTERI - Audry Santoso (Jurnal Health Sains, 2023)
The maternal mortality rate in Indonesia in 2012 was still quite high, reaching 32 per 100,000 births. According to the Ministry of Health of the Republic of Indonesia in 2010, deaths due to postpartum hemorrhage reached 40-60% (Ministry of Health RI, 2010). Reports on Maternal Mortality districts/cities in East Java, showed that the MMR in East Java in 2012 was 97.43 per 100,000 live births, with the death rate being caused by bleeding by 33.06%. Meanwhile, the incidence of postpartum hemorrhage in the city of Surabaya reached 16.67% (DinKes Kota, 2009). In 80 to 90 percent of postpartum hemorrhage the main cause and most are due to uterine atony (absence of contractions in the uterus/womb), with a percentage of 50-60% (Varney, 2007). Woman, aged 28 years, came with complaints of uncontrolled bleeding after giving birth 5 days ago at the midwife. Spontaneously born baby, immediately crying loudly, male sex, weight 3900 g, followed by delivery of the placenta. On physical examination, the general condition was weak, composure, blood pressure 110/70 mmHg, pulse 113 x/minute, respiration 22 x/minute, temperature 36.6 °C. In general status obtained pale conjunctiva and cold acral. On obstetric examination found weak contractions, no tenderness. Examination of the lower portion is found lividae, open external urethral orifice (OUE), active bleeding, positive lacerations, positive hecting. Supporting examination showed a presemce of low Hb that is 4.6 g/dl. The patient was diagnosed as P1A0 spontaneous postpartum 5 days with HPP ec rest of placenta + uterine atony + anemia..